Impact of the motor function of individuals with spinal muscular atrophy on caregiver burden - Natália Guimarães Melo; Geovane Balçanufo de Souza e Silva; Cecília Rosa de Ávila; Francine Aguilera Rodrigues da Silva; Maysa Ferreira Martins Ribeiro; Letícia de Araújo Morais (Universidade de São Paulo, 2023)
ABSTRACT Spinal Muscular Atrophy (SMA) is a neurodegenerative disease that impairs motor function, justifying the help of a caregiver. This study aimed to analyze the impact of the motor function of individuals with SMA on caregiver burden. This is a cross-sectional study of 32 individuals with SMA and 27 caregivers, carried out in a rehabilitation center, using the identification questionnaire, anamnesis and sociodemographic profile, Motor Function Measurement Scale and Burden Interview. Motor function and caregiver burden were compared between SMA types using the analysis of covariance (ANCOVA) and correlated using Pearson's correlation test. Individuals with SMA type I had greater impairment of motor function when compared to types II and III, and individuals with type III had better scores in all domains of motor function. No correlation was observed between motor function and caregiver burden: however, most caregivers presented some level of burden, especially those from mild to moderate. Moderate to severe burden was found in caregivers with SMA in a considerable prevalence, which requires care and attention from health professionals.